2017
DOI: 10.1016/j.jalz.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic features of TOMM40 '523 variant on late‐life cognitive decline

Abstract: INTRODUCTION The study investigated the role of neuropathologies in the relationship between TOMM40 ‘523 genotype and late life cognitive decline. METHODS Participants were community-dwelling older persons who had annual cognitive assessments and brain autopsies after death. Genotyping used DNA from peripheral blood or postmortem brain tissue. Linear mixed models assessed the extent to which the association of ‘523 genotype with cognitive decline is attributable to neuropathologies. RESULTS Relative to ε3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…We examined the effects of the TOMM40 haplotypes to cognitive decline, incident AD, and neuropathology [143146]. Due to its strong linkage disequilibrium with APOE we restricted one analysis of Caucasians to persons with APOE ε3/3 genotype and found that both ‘523-L and ‘523-S/S S/S poly-T genotype were related to faster cognitive decline, especially episodic memory, a finding similar to APOE4 [146]. In another study we examined racial differences and found that among Caucasians nearly all APOE4 carriers had ‘523-L whereas less than half of the African Americans had this haplotype [144].…”
Section: Resultsmentioning
confidence: 99%
“…We examined the effects of the TOMM40 haplotypes to cognitive decline, incident AD, and neuropathology [143146]. Due to its strong linkage disequilibrium with APOE we restricted one analysis of Caucasians to persons with APOE ε3/3 genotype and found that both ‘523-L and ‘523-S/S S/S poly-T genotype were related to faster cognitive decline, especially episodic memory, a finding similar to APOE4 [146]. In another study we examined racial differences and found that among Caucasians nearly all APOE4 carriers had ‘523-L whereas less than half of the African Americans had this haplotype [144].…”
Section: Resultsmentioning
confidence: 99%
“…Biomarkers and neuropathological features that track the progression of LOAD or correlate with changes in cognition assist with development of testable hypotheses to elucidate the biological mechanisms that underlie genetic associations. To interpret the autonomous association of the TOMM40 poly-T with LOAD, recently, Yu et al investigated the neuropathologic features associated with TOMM40 - APOE haplotypes in a large cohort of community-dwelling older persons who had annual cognitive assessments and brain autopsies after death[55]. First, they assessed the independent effect of the TOMM40 poly-T using the APOE ε3/3 stratum, and found that individuals carrying the TOMM40 poly-T S/S genotype had faster cognitive decline relative to the S/VL or VL/VL genotypes, consistent with their previous report [31] and pointing to the S allele as the risk allele for the cognitive decline phenotype[55].…”
mentioning
confidence: 99%
“…To interpret the autonomous association of the TOMM40 poly-T with LOAD, recently, Yu et al investigated the neuropathologic features associated with TOMM40 - APOE haplotypes in a large cohort of community-dwelling older persons who had annual cognitive assessments and brain autopsies after death[55]. First, they assessed the independent effect of the TOMM40 poly-T using the APOE ε3/3 stratum, and found that individuals carrying the TOMM40 poly-T S/S genotype had faster cognitive decline relative to the S/VL or VL/VL genotypes, consistent with their previous report [31] and pointing to the S allele as the risk allele for the cognitive decline phenotype[55]. Comparing the effect size of the TOMM40 poly-T S allele on cognitive decline to that of the APOE ε4// TOMM40 poly-T L, indicated that the former effect size is smaller by approximately 40%.…”
mentioning
confidence: 99%
“…Co-localized genetic markers TOMM40 and APOE [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 151 , 153 ] which account for the vast majority of variability in both risk and age-of-onset of the disease ( Figure 12 ) is useful for the prediction of age of AD onset. It is proposed that each of the original AD age of onset curves is a composite of sub-curves that are defined by TOMM40 genotype.…”
Section: Introductionmentioning
confidence: 99%